Clinical applications of antimicrobial photodynamic therapy in dentistry - Gholami, Leila; Shahabi, Shiva; Jazaeri, Marzieh; Hadilou, Mahdi; Fekrazad, Reza (Frontiers in Microbiology, 2023)
Given the emergence of resistant bacterial strains and novel microorganisms that globally threaten human life, moving toward new treatment modalities for microbial infections has become a priority more than ever. Antimicrobial photodynamic therapy (aPDT) has been introduced as a promising and non-invasive local and adjuvant treatment in several oral infectious diseases. Its efficacy for elimination of bacterial, fungal, and viral infections and key pathogens such as Streptococcus mutans, Porphyromonas gingivalis, Candida albicans, and Enterococcus faecalis have been investigated by many invitro and clinical studies. Researchers have also investigated methods of increasing the efficacy of such treatment modalities by amazing developments in the production of natural, nano based, and targeted photosensitizers. As clinical studies have an important role in paving the way towards evidence-based applications in oral infection treatment by this method, the current review aimed to investigate and summarize the available randomized controlled clinical studies conducted on the applications of aPDT and investigate its future horizons in the dental practice through a comprehensive search in literature. Four databases including PubMed (Medline), Web of Science, Scopus and Embase were searched up to September 2022 to retrieve related clinical studies. There are several clinical studies reporting aPDT as an effective adjunctive treatment modality capable of reducing pathogenic bacterial loads in periodontal and peri-implant, and persistent endodontic infections and showing positive effects on reduction of microbial pathogens associated with these infections. Clinical evidence also reveals a therapeutic potential for aPDT in prevention and reduction of cariogenic organisms and treatment of infections with fungal or viral origins, however, the number of clinical studies in these groups are much less. Altogether, various photosensitizers have been used and it is still not possible to recommend specific irradiation parameters due to heterogenicity among studies. Reaching effective clinical protocols and parameters of this treatment is difficult and requires further high quality randomized controlled trials focusing on specific PS and irradiation parameters that have shown to have clinical efficacy and are able to reduce pathogenic bacterial loads with sufficient follow-up periods.